Got sun? Go solar : harness nature's free energy to heat and power your grid-tied home - Ewing, Rex A. (PixyJack Press, 2009)
Examines renewable energy options for grid-tied homeowners, including solar and wind generated electricity, solar water heating, passive solar, and geothermal heating/cooling. System configurations and equipment, average costs, financial incentives, and installation considerations are also covered--Provided by publisher.